The development of introgression lines of Triticum timopheevii in a cultivated wheat background and their characterisation - Devi, Urmila (2018)
Achieving a sustainable supply of food in the face of the rise in the global population and climate change is a major challenge for plant breeders. Crop improvement through breeding is only possible where genetic variation is present in the breeder’s germplasm, but decades of intensive selection in major crops has inevitably narrowed their genetic diversity. The efficient use of the biodiversity of wild relatives of wheat is key for the enhancement of genetic variability. Many wild relatives of wheat possess a vast potential reservoir of genetic variation for abiotic and biotic stresses e.g. drought tolerance, resistance to insects and fungal diseases, biomass, yield and photosynthetic potential. Triticum timopheevii is a tetraploid wheat (2n=28, AtAtGG), which is characterized by complex resistance genes to many diseases. Genes for resistance to stem rust (Sr36), powdery mildew (Pm2, Pm6, Pm27) and leaf rust (Lr18) have been exploited. Hence, it has been used in this programme with the prime objective of developing chromosome introgression lines for the At and G genomes of T. timopheevii in bread wheat. Characterization of wheat/T. timopheevii introgression lines was carried out via an Axiom® 35K SNP wild relative array. A putative linkage map of T. timopheevii has been successfully developed and confirmed by exploitation of fluorescence in situ hybridization (FISH). Development of wheat chromosome specific KASP markers which will aid in further characterization of the introgressions is underway. T. timopheevii accession assessed for mineral concentrations demonstrated variation which can be further exploited in wheat breeding micronutrients. Variations for Fusarium head blight (FHB) in accessions of T. timopheevii were also demonstrated and mapping populations developed to map the resistance genes for FHB. The results show the presence of novel type I resistance present in T. timopheevii. Mapping of FHB resistance genes with KASP markers is underway.